(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the extend of business support environment in Slovenia terms of geography, number of different entities and sources of financing? Purpose: The purpose of our research is to establish the extend of Slovenia’s business support environment (ecosystem) for start-ups. The research focuses on geographical areas, types of entities and sources of financing. Method: First the existing literature and web pages of individual entities working in the area of business support environment were checked. A list of all entities was prepared and analysed with which activities they supported start-ups. Results: The research showed that Slovenia’s business support environment for start-ups is stronger in some geographical areas than others. In addition, the majority of business support entities are not specialized for specific needs of start-ups, they also support regular businesses which means their support is not ideal. The majority of business support entities was funded by public money and even private entities are mostly financed with money coming from public tenders. Organization: We believe our research will help the business support environment identify critical areas that need to be strengthened thus enabling a better support in all growth-phases for start-ups. Society: Economic activity and establishment of successful businesses greatly influence the success of society and its social environment. Successful businesses serve people as means of prosperous life and enable them to realize their potential. Start-up businesses have a great potential for growth and development. Originality: In our opinion the originality of research lies in two aspects: it delivers an analysis of Slovenia’s business support environment, including some new factors which gives a new view of the topic. On the other side the research identifies certain drawbacks of the current system that present difficulties for start-up owners. Limitations/Future Research: Due to its broad scope, the research is limited only to Slovenia and its business support environment. In addition the data was gathered from websites and publications and was not checked personally for each entity.